Multi Criteria Supplier Selection from Social Aspects in Thai Tyre Rubber Industry - Srinual, Napat; Mehnen, Jorn; Udomsub, Rapee (Business Administration and Management Journal Review, 2020)
One of the main issues for companies and organisations is choosing the most appropriate supplier regarding social issues. Besides traditional criteria, companies started to focus on social issues in supplier selection. The methods of group decision making are well established approaches to tackle this issue which could allow decision makers to determine socially selected suppliers’ problems. Many existing researches, nonetheless, encompasses scant review of ambiguity which is involved in the process of selecting suppliers. Hence, this study aims to propose a method combines the strength of the Fuzzy sets to deal with an uncertainty or vagueness with AHP-TOPSIS approach to select suppliers by concerning social aspects. AHP method used to identify criteria weights and TOPSIS approach is utilized to sort and select the best appropriate supplier. According to the literature review and company requirements, the criteria in social perspectives was developed to eight criteria. This study uses the questionnaire to gather data from top five manager’s judgements who had been chosen based on purposive and self-selection sampling in each department. A case study was carried out in Thailand in the Tyre rubber sector to validate result. The findings demonstrate that Job security (34%) is the most important criteria, following by Employees’ health and safety (16%) and Training programs (12%) respectively. The study also presents that “Supplier D” is the most suitable supplier above other suppliers.